The Concept of Forced Defense As Legal Protection Against the Criminalization of Crime Victims - Suriadiata, Irpan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Article 49 of the Indonesian Criminal Code (KUHP) governs the concept of compelled defense, also known as "noodweer" in Dutch terminology. This article offers legal protection for individuals who engage in an unlawful conduct, such as abuse or murder, but do so in self-defense or in defense of another person who is under a severe threat to their life or physical well-being. The objective of this study is to ascertain the manner in which investigators constructed the legal framework to identify the suspect responsible for the abuse crime in the case that transpired at Yayasan Al-Amin NW Kilang in District Montong Gading, East Lombok district, West Nusa Tenggara on July 19, 2022, and to determine whether the suspect's actions constituted a forced defense in accordance with the provisions outlined in article 49, paragraph 1 of the Criminal Code. The present case study was authored utilizing analytical descriptive techniques in conjunction with empirical-normative research methods. The research findings indicate, initially, that the investigator's subjective elements significantly influence the trajectory of the investigation in the a-quo case. Consequently, the investigator formulates questions for the investigation in a manner that is streamlined solely to satisfy and substantiate the requirements outlined in Article 351 paragraph of the Criminal Code and to identify the suspect. The second criminal act of abuse pertains to the suspect's assault, which satisfies the criteria for a forced defense as defined in article 49 of the Criminal Code, provided that a-quo is satisfied.